Angiographic embolization in epistaxis: Our clinical experience and results (Annals of Medical Research, 2021)
Aim: Nosebleed, more commonly called epistaxis is a general clinical problem, and the most of bleedings can be treated non-invasive approach. However, because of persistent and sometimes life-threatening bleeding, additional treatment such as super-selective embolization may be required. In this study, we report our data on the endovascular treatment of persistent epistaxis.Materials and Methods: Between January 2010 and December 2019, all patients who were followed up at Inonu University Turgut Ozal Medical Center Otorhinolaryngology Clinic due to recurrent persistent nosebleed and required endovascular treatment were retrospectively screened. Demographic data, cause of epistaxis, localization of the bleeding, the clinical significance of the bleeding, interventional approach, complications related to treatment, and results were evaluated.Results: All of 18 patients with intractable epistaxis were included in the study. Depending on the etiology of epistaxis, patients were determined into three groups: idiopathic epistaxis (10/18), iatrogenic or traumatic epistaxis (7/18), and nasopharyngeal cancer (1/18). Nine of 18 patients required blood transfusions. The internal maxillary artery was embolized unilaterally in 12 of 18 (66%) and bilaterally in 2 of 18 (11%) procedures. Four patients were not embolized because of bleeding originated from ethmoidal branches of the ophthalmic artery. These four patients were operated on (endoscopic ethmoidectomy and bleeding control). Long-term success rates of embolization were 14 of 14. Major complications (transient hemiparesis) occurred in one patient after embolization.Conclusion: Endovascular approach proves to be effective for intractable and fatal epistaxis. Embolization has a good risk-benefit ratio in persistent bleeding. However, if bleeding is originated by the ethmoidal branches of the ophthalmic artery, embolization may not be performed to avoid visual complications.